The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s40268-015-0110-z
|View full text |Cite
|
Sign up to set email alerts
|

Trimester-Specific Population Pharmacokinetics and Other Correlates of Variability in Sulphadoxine–Pyrimethamine Disposition Among Ugandan Pregnant Women

Abstract: BackgroundSulphadoxine–pyrimethamine (SP) is widely used as an intermittent preventive treatment for malaria in pregnancy (IPTp). However, pharmacokinetic studies in pregnancy show variable and often contradictory findings. We describe population and trimester-specific differences in SP pharmacokinetics among Ugandan women.MethodsSP (three tablets) were administered to 34 nonpregnant and 87 pregnant women in the second trimester. Seventy-eight pregnant women were redosed in the third trimester. Blood was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
4
8
1
Order By: Relevance
“…The two lowest values of these parameters were from the groups from Zambia and Mali in which postpartum studies were performed relatively early (36). In contrast, the largest values were from studies (including the present study) that incorporated a nonpregnant matched comparator group (46). This suggests that a significant reduction in SDOX exposure during pregnancy may be missed if comparative postpartum pharmacokinetic data are collected close to delivery.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The two lowest values of these parameters were from the groups from Zambia and Mali in which postpartum studies were performed relatively early (36). In contrast, the largest values were from studies (including the present study) that incorporated a nonpregnant matched comparator group (46). This suggests that a significant reduction in SDOX exposure during pregnancy may be missed if comparative postpartum pharmacokinetic data are collected close to delivery.…”
Section: Discussioncontrasting
confidence: 56%
“…In three groups, there was a higher PYR exposure in pregnancy (Mali, Mozambique, and Zambia [36]), two showed no effect of pregnancy (Sudan and Kenya [36,39]), and two showed a lower exposure in pregnancy (PNG and Uganda [34,46]; see Table 8). Nyunt et al have suggested three potential mechanisms that might account for these discrepancies (36).…”
Section: Discussionmentioning
confidence: 99%
“…Potential confounders not included in the original modeling reduced, but did not eliminate, between‐site differences in pharmacokinetic parameters. For sulfadoxine, there was an overall threefold higher clearance during pregnancy vs. that after delivery, consistent with other available data2, 3, 4 and reflecting pregnancy‐associated physiological changes 1. Pyrimethamine clearance was, by contrast, 18% lower in pregnancy compared with the postpartum period, with a reduced area under the plasma concentration‐time curve (AUC) after delivery 1…”
Section: Figuresupporting
confidence: 87%
“…This suggests strongly that lactating women are not metabolically equivalent to nonpregnant women in the case of pyrimethamine. The reduced pyrimethamine clearance in pregnancy relative to that postpartum, as reported by de Kock et al .,1 does not, therefore, contradict other studies using nonpregnant women as the comparator group that showed increased pyrimethamine clearance and a lower AUC 3, 4…”
Section: Figurementioning
confidence: 60%
See 1 more Smart Citation